RADIOGRAPHY TECHNIQUE OF OSSA PELVIS WITH SUSPECTED FRACTURE OF OS PUBIS IN RADIOLOGY INSTALLATION OF EFARINA ETAHAM HOSPITAL, BERASTAGI, KARO DISTRICT, IN 2020 - Wahyuni Tarigan, Sri; Zysman, John; Yunardi, Yunardi; Sastri Mara, Dilla; Maswan, Maswan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
Fractures are broken bones, usually caused by trauma or physical exertion, the force and angle of the force, the condition of the bone itself, and the soft tissue around the bone will determine whether the fracture is complete or incomplete. A complete fracture occurs when the entire bone is broken, whereas an incomplete fracture does not involve the entire thickness of the bone. There are several terms used to describe the type of fracture, namely: Transverse Fractures, Longitudinal Fractures, Segmental Fractures, Compression Fractures and Avulsion Fractures. The examination aims to determine the results of radiographic images, if a fracture or collision occurs and is caused by an KLL factor (traffic accident). The aim of the study was to find out how the technique for radiographic examination of the Ossa Pelvis with the suspicion of Oss Pubis Fracture at the Radiology Installation of Efarina Berastagi Hospital in 2020. This type of research is descriptive research with data collection techniques by observation, documentation study and literature (library) study. The results of the examination of the Ossa Pelvis with the suspicion of Oss Pubic Fracture at the Radiology Installation of Efarina Etaham Berastagi Hospital are generally using the AP (Anterior Posterior) projection. The ideal X-Ray device for Ossa Pelvis radiography is a portable X-Ray unit or mobile X-Ray unit with relatively low capabilities. The x-ray film used is a high speed type combined with a fast screen intensifying (IS) where this type of film and intensifying screen (IS) can produce images with good detail and sharpness. Thus the radiation dose can also be reduced for the patient and the operator himself. The x-ray film washing process used should use Automatic Processing. It is hoped that it can be used as a reference for radiographic results, especially in cases of Os Pubis Fractures.